Effect of Natural Farming on Wheat Productivity and Physico-chemical and Biological Properties of a Vertisol of Vidisha District of Madhya Pradesh - Raghuwanshi, H. S.; Jaga, P. K.; Dwivedi, B. S.; Kurmi, Prashant; Tripathi, P. N.; Thakur, R. K. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during the month of October in the Rabi season of 2023–24 at the Research Field of the College of Agriculture, Ganj Basoda, District Vidisha, Madhya Pradesh, India to evaluate the effect of natural farming on the productivity of wheat and soil health. The experiment was laid out in a Randomized Block Design (RBD) with eight treatments (organic inputs) and three replications. The treatments included T1 (Control), T2 (Ghanjeevamrit @ 5q ha-1 before sowing), T3 (Jeevamrit @ 20% foliar application at 21-day intervals), T4 (Mulching @ 10 t ha-1), T5 (Ghanjeevamrit+Jeevamrit), T6 (Ghanjeevamrit+Mulching), T7 (Jeevamrit+Mulching), and T8 (Ghanjeevamrit+Jeevamrit+Mulching). The highest grain and straw yields of wheat were recorded under Ghanjeevamrit+Jeevamrit+Mulching treatment, whereas the lowest grain and straw was observed in the Control plot. Similarly, yield attributes such as number of grains per spike and test weight were the highest under Ghanjeevamrit+Jeevamrit+Mulching, indicating improved crop performance with integrated natural farming inputs. It was also observed that treatment Ghanjeevamrit+Jeevamrit+Mulching resulted in the highest microbial count and dehydrogenase enzyme activity, suggesting an enhancement for soil biological health. These findings suggest that the combined application of Ghanjeevamrit, Jeevamrit, and Mulching can enhance both crop yield and soil health, making it a promising strategy for sustainable crop production.